2005
DOI: 10.1080/08860220500198037
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Demodex Folliculorum in Patients with End Stage Chronic Renal Failure

Abstract: Our findings indicate that the DF number is increased in ESRF patients on dialysis treatment. We recommend that demodicidosis should be included in the differential diagnosis of facial eruptions in patients with ESRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 28 publications
0
34
2
5
Order By: Relevance
“…In our study DF density was 5.11 ± 5.65/cm 2 in patients and 2.55 ± 1.6/cm 2 in controls. DF density in our controls was higher than in Karincaoglu's study 19 …”
Section: Discussioncontrasting
confidence: 78%
“…In our study DF density was 5.11 ± 5.65/cm 2 in patients and 2.55 ± 1.6/cm 2 in controls. DF density in our controls was higher than in Karincaoglu's study 19 …”
Section: Discussioncontrasting
confidence: 78%
“… 76 have observed a higher incidence of high Dd (≥5 D/cm 2 ) in patients receiving chemotherapy than in a control group, and Karincaoglu et al. 77 have observed that the Dd is higher in patients with end stage chronic renal failure (6.12 D/cm 2 , n = 62) than in the control patients (0.31 D/cm 2 , n = 62) ( P = 0,000). Other factors like erythematotelangiectatic rosacea, skin temperature, 56 lack of soap, 12,15,64,70 or thick layers of make‐up, 15,70 and sebaceous hyperplasia could also favour D proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…Rosaceiform dermatitis has been reported following repeated facial application of topical steroids and other immunomodulators with similarly increased numbers of mites recorded [13] . Several other studies have shown that Demodex mite numbers are increased in immunosuppressed patients, children with leukaemia receiving chemotherapy [14] , patients with HIV infection and AIDS [15,16] , patients undergoing phototherapy [17] and patients on chronic dialysis [18] .…”
mentioning
confidence: 99%